(3YQV hJMdjd eY eONd HOjds - (3Ydj eMeO(B, (3YHO GdhgGHs; (3SYjO jS YGeQ(B, s ((3GdQjGV(B:s (3OGQ GdeQjN ddfTQ(B,s, 1984)
(3CSS eMGSHI GdehGQO GdHTQjI, eMGSHI GdehGQO GdHTQjI heTcdGJ GdJWHjb, eONd HOjd deMGSHI GdehGQO GdHTQjIs
(3HHdjhZQGajG(B: (3U(B.98s
Keywords: (3EOGQI GdCaQGOs; (3GdeMGSHIs; (3GdehGQO GdHTQjIs